Non-stationary Responses of Tree-Ring Chronologies and Glacier Mass to Climate in the European Alps - G. LEONELLI; M. PELFINI; R. D’ARRIGO; W. HAEBERLI; P. CHERUBINI (Arctic, Antarctic, and Alpine Research, 2011)
Tree-ring width and glacier mass balance are two highly sensitive climatic proxies which are often used as indicators of biological and geophysical changes in high-altitude ecosystems. Tree-ring data have been widely used to reconstruct past temperatures and also to reconstruct past glacier mass balance. Here we show that tree-ring chronologies from a high-altitude Pinus cembra L. dendroclimatic network and glaciers from the same region in the European Alps have non-stationary responses to air temperature, and have also been responding non-proportionally to temperature extremes in recent decades. Both ring-width chronologies and the mass-balance series of some glaciers from the same region have shown an increasing sensitivity to summer (JJA) temperatures. Our results demonstrate that the sensitivity to climate of tree-ring chronologies and glacier mass balance may change over time and has been increasing in recent decades, posing some limitations to tree-ring-based glacier mass-balance reconstruction. Moreover, we found these reconstructions in the European Alps are more reliable for large rather than for small glaciers, and may not be able to reveal years of extreme ablation that could have occurred in the past.